Additions to Philippine Slender Skinks of the Brachymeles bonitae Complex (Reptilia: Squamata: Scincidae) III: a new species from Tablas Island - Davis, Drew R.; Geheber, Aaron D.; Watters, Jessa L.; Penrod, Michelle L.; Feller, Kathryn D.; Ashford, Alissa; Kouri, Josh; Nguyen, Daniel; Shauberger, Kathryn; Sheatsley, Kyra; Winfrey, Claire; Wong, Rachel; et al. (Zootaxa, 2016)
Studies of the diversity of Philippine amphibians and reptiles have resulted in the continued description of cryptic species. Species formerly thought to range across multiple recognized faunal regions are now considered to be assemblages of multiple unique species, each restricted to a single faunal region. This pattern continues to hold true when considering Philippine skinks of the genus Brachymeles. Recent studies have resulted in the description of numerous unique species with many exhibiting various degrees of digit loss or limb reduction, as well as suggesting that unique lineages are still present in the B. bonitae Complex. In this paper, we describe a new species of fossorial skink within this species complex from Tablas Island based on collections made nearly 50 years ago. Although no genetic data are available for the new species, examinations of morphological data (qualitative traits, meristic counts, and mensural measurements) support its distinction from all other members of the genus. Brachymeles dalawangdaliri sp. nov. is differentiated from other members of the genus based on a suite of unique phenotypic characteristics, including a small body size (SVL 66.0–80.9 mm), bidactyl fore-limbs, digitless, unidactyl, or bidactyl hind limbs, a high number of presacral vertebrae (49), the absence of auricular openings, and distinct dorsal head scale patterns. The description of the new species increases the diversity of endemic vertebrates recognized to occur in the Romblon Island Group in the central Philippines.